WHO guidance on COVID-19 vaccine trial designs in the context of authorized COVID-19 vaccines and expanding global access: Ethical considerations. Issue 14 (25th March 2022) - Singh, Jerome Amir; Kochhar, Sonali; Wolff, Jonathan; Atuire, Caesar; Bhan, Anant; Emanuel, Ezekiel; Faden, Ruth; Ghimire, Prakash; Greco, Dirceu; Ho, Calvin; Moon, Suerie; Shamsi-Gooshki, Ehsan; et al.
Abstract: While the degree of COVID-19 vaccine accessibility and uptake varies at both national and global levels, increasing vaccination coverage raises questions regarding the standard of prevention that ought to apply to different settings where COVID-19 vaccine trials are hosted. A WHO Expert Group has developed guidance on the ethical implications of conducting placebo-controlled trials in the context of expanding global COVID-19 vaccine coverage. The guidance also considers alternative trial designs to placebo controlled trials in the context of prototype vaccines, modified vaccines, and next generation vaccines.